2014
DOI: 10.1086/677628
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Reduced Chlorhexidine Susceptibility in Organisms Causing Central Line–Associated Bloodstream Infections

Abstract: In units that bathe patients daily with chlorhexidine gluconate (CHG), organisms causing central line-associated bloodstream infections (CLABSIs) were more likely to have reduced CHG susceptibility than organisms causing CLABSIs in units that do not bathe patients daily with CHG (86% vs 64%; P = .028). Surveillance is needed to detect reduced CHG susceptibility with widespread CHG use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
60
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 9 publications
3
60
0
1
Order By: Relevance
“…Levels within the reported range of chlorhexidine MIC for enterococci (25)(26)(27)(28)(29) were detected on patient skin (24). In another study, chlorhexidine susceptibilities were monitored for CLABSI enterococcal isolates obtained from hospital wards using chlorhexidine bathing (30). It was observed that the chlorhexidine MIC increased significantly in those isolates compared to CLABSI isolates from nonbathing wards (30).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Levels within the reported range of chlorhexidine MIC for enterococci (25)(26)(27)(28)(29) were detected on patient skin (24). In another study, chlorhexidine susceptibilities were monitored for CLABSI enterococcal isolates obtained from hospital wards using chlorhexidine bathing (30). It was observed that the chlorhexidine MIC increased significantly in those isolates compared to CLABSI isolates from nonbathing wards (30).…”
mentioning
confidence: 97%
“…In another study, chlorhexidine susceptibilities were monitored for CLABSI enterococcal isolates obtained from hospital wards using chlorhexidine bathing (30). It was observed that the chlorhexidine MIC increased significantly in those isolates compared to CLABSI isolates from nonbathing wards (30). The results of both studies indicate that enterococci are exposed to subinhibitory chlorhexidine concentrations in clinical settings as a result of chlorhexidine bathing.…”
mentioning
confidence: 99%
“…A number of genes exist within S. aureus, most notably qacA or qacB (qacA/B) and smr, which encode multidrug efflux pumps whose presence is associated with higher minimum bactericidal concentrations (MBCs) of chlorhexidine and other antiseptics. Suwantarat et al (16) showed that these organisms existed at a higher prevalence in hospital units performing daily chlorhexidine bathing than in those units that did not. Studies at our own institution showed an increase in the proportion of S. aureus isolates with antiseptic tolerance following an increase in chlorhexidine use among oncology and cardiac surgery patients (17,18).…”
mentioning
confidence: 99%
“…Finally although mupirocin and chlorhexidine resistance did not increase in our study or the REDUCE-MRSA trial [4], there is new concern that exposure to chlorhexidine might be associated with colistin resistance [8]. To the Editor-We read with great interest the study by Klompas et al suggesting that a very short course of antimicrobial therapy (1-3 days) might not be associated with a higher risk of ventilator or hospital death in patients with suspected ventilator-associated pneumonia (VAP), compared with a longer course [1]. We discuss some potential limitations of the study.…”
mentioning
confidence: 88%
“…To the Editor -Despite heightened concern for increased resistance to mupirocin and chlorhexidine [1][2][3][4], reports that assess the relationship between consumption of the agents and genotypic resistance are scarce. We sought to determine if there were any significant trends in mupirocin and chlorhexidine consumption in the nationwide healthcare system of the US Department of Defense (DOD) and in a subset of DOD hospitals in the National Capital Region (DOD-NCR) that also conduct active surveillance for mupA and qacA/B.…”
mentioning
confidence: 99%